Mucociliary interactions and mucus dynamics in ciliated human bronchial epithelial cell cultures - Sears, Patrick R.; Davis, C. William; Chua, Michael; Sheehan, John K. (American journal of physiology. Lung cellular and molecular physiology, 2011)
The airway epithelial surface liquid is generally considered to be composed of two layers, a periciliary layer and a continuous thick mucus layer moving in bulk. This view may not be appropriate for all areas of the lung. Our hypothesis, that mucus may form a discontinuous layer with dynamic attachments to the surface, is investigated using a culture system. We used live-cell confocal microscopy to investigate thin mucus layers and fluorescent beads and exogenous MUC5B to visualize mucus dynamics on ciliated human bronchial cultures. A continuous mucus layer was not observed. In sparsely ciliated cultures, mucus attached to ciliated cells; however, in highly ciliated cultures, mucus formed strands several hundred micrometers long. As with increases in ciliation, increases in bead concentration caused the appearance of mucus strands. We confirmed the involvement of mucins in the binding of mucus to cilia by adding labeled purified MUC5B to the cultures. These data suggest that mucins may have an intrinsic ability to form attachments to cilia. The significance of these findings is that aberrant modulation of such an intrinsic property may explain the initiation of highly adherent mucus in cystic fibrosis lung disease.